2021
DOI: 10.20944/preprints202108.0053.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protective Factors and Teachers’ Risk to Burnout during the Covid-19 Pandemic. Do Kolb’s Educator Roles Matter? - A Cluster Analysis

Abstract: Teacher burnout has been revealed to be one of the most common negative consequence of the COVID-19 pandemic The purpose of this study was to identify distinct psychological resources and burnout risk profiles of teachers and to examine their association with Kolb’s Educator Roles and the professional experience. Methods: The survey data were collected from 330 preschool and primary school (84 males, Mage = 38.3, SD = 9.14) teachers using a convenience sampling method. Results: The two-step cluster a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Most of the studies in the educational field have focused on the inverse relationship between emotional intelligence and teachers’ burnout 69 . In a previous study, we even identified positive emotionality, well-being and self-control, basic traits of emotional intelligence, as the main protective factors against experiencing burnout 70 . However, the experience of burnout symptoms also depends on other internal factors besides teachers’ emotional intelligence 26 .…”
Section: Discussionmentioning
confidence: 91%
“…Most of the studies in the educational field have focused on the inverse relationship between emotional intelligence and teachers’ burnout 69 . In a previous study, we even identified positive emotionality, well-being and self-control, basic traits of emotional intelligence, as the main protective factors against experiencing burnout 70 . However, the experience of burnout symptoms also depends on other internal factors besides teachers’ emotional intelligence 26 .…”
Section: Discussionmentioning
confidence: 91%
“…First, when interpreting results, it is important to consider the high-stress context for this study, which occurred in the aftermath of the sudden transition to virtual instruction during the COVID-19 pandemic. During this time, school staff faced a drastic and sudden re-configuration of their job demands and were called on to translate instructional content to online platforms, and coordinate adequate resources for individual students ( García-Carmona et al, 2019 ; Rǎducu and Stǎnculescu, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that the fear of losing employment or income, losing loved ones, or experiencing serious and even life threatening health problems are among the most intense negative emotions seen during the pandemic [ 24 ]. On the other hand, Răducu and Stănculescu [ 25 ] stated that teachers’ feelings of burnout are among the most common negative emotional states reported during the pandemic period.…”
Section: Literature Reviewmentioning
confidence: 99%